PdtaS Deficiency Affects Resistance of Mycobacteria to Ribosome Targeting Antibiotics - Dadura, Karolina; Płocińska, Renata; Rumijowska-Galewicz, Anna; Płociński, Przemysław; Żaczek, Anna; Dziadek, Bożena; Zaborowski, Andrzej; Dziadek, Jarosław (Frontiers in Microbiology, 2017)
Two-component regulatory systems (TCSSs) are key regulatory elements responsible for the adaptation of bacteria to environmental stresses. A classical TCSS is typically comprised of a sensory histidine kinase and a corresponding response regulator. Here, we used homologous recombination to construct a Mycobacterium smegmatis mutant defective in the synthesis of cytosolic histidine kinase PdtaS (Msmeg_1918). The resulting ΔpdtaS mutant strain was tested in the Phenotype Microarray screening system, which allowed us to identify aminoglycoside antibiotic sensitivity, tetracyclines antibiotic resistance as well as membrane transport and respiration, as the main processes affected by removal of pdtaS. The antibiotic sensitivity profiles were confirmed by survival assessment and complementation studies. To gain insight into the molecular mechanisms responsible for the observed phenotype, we compared ribosomal RNA and protein profiles of the mutant and wild-type strains. We carried out Northern blotting and qRT-PCR to compare rRNA levels and analyzed ribosome sedimentation patterns of the wild-type and mutant strains on sucrose gradients. Isolated ribosomes were further used to estimate relative abundance of individual proteins in the ribosomal subunits using label free mass spectrometry analysis. Additionally, the ΔpdtaS mutant revealed lower activity of the respiratory chain as measured by the rate of TTC (triphenyltetrazolium chloride) reduction, while at the same time showing only insignificant changes in the uptake of aminoglycosides. We postulate that deficiency of PdtaS affects the oxidative respiration rates and ribosomal composition causing relevant changes to intrinsic resistance or susceptibility to antibiotics targeting ribosomes, which are commonly used to treat mycobacterial infections.